Risk factors of gallbladder cancer in Nepal: A case control study - Chanda Thakur; Roshan Kumar Mahato; Sabina Marasini; Dinesh Timalsena; Krishna Sagar Sharma; Biraj Man Karmacharya (PLoS ONE, 2025)
Background Gallbladder cancer (GBC) is a rare, highly fatal disease with diagnosis in advanced stage and low survival rate. Nepal ranked 4th position with highest rates of GBC for 10 countries in 2020. Objective To find the association between socio-demographic, behavioral and environmental factors associated with the development of GBC. Method A case-control study was conducted in 2021/22 with newly diagnosed gallbladder cancer cases from three cancer-specialized hospitals and one tertiary (superspeciality) hospital. Controls were selected from the same tertiary hospital and one additional hospital providing services to gallbladder pathologies for a huge population, making a total of five hospitals involved in the study. The ratio of cases to control was 1:1. The data collection was done through telephonic interviews using structured questionnaires. The risk factors for GBC were assessed by using unconditional logistic regression to find odds ratios and 95% confidence level for bivariate and multivariate analysis. The statistical analysis was carried out in STATA 18. Result A total of 240 respondents were enrolled in the study, among them half were GBC patients (cases) and half were gallbladder patients (controls). The average age of the respondents was 54.82±12.3 years, with female preponderance among both groups. On multivariate analysis, the risk factors studied were; parity ≥3 (AOR = 2.80, 95% CI: 1.17–6.66, P value 0.020), being ethnic group of Terai/Madhesi (AOR = 7.88, 95% CI: 3.16–19.66, P value <0.001), being Janajati (AOR = 3.36, 95% CI: 1.17–6.61, P value <0.001), having gallbladder related disease (AOR = 2.00, 95% CI:1.00–4.02, P value 0.049), consuming alcohol ≥100ml/day (AOR = 3.44, 95% CI:1.11–10.63, P value 0.032), exposed with pesticides ≥2 times in a year (AOR = 4.04, 95% CI: 1.27–12.89, P value 0.018) and consuming less vegetables and fruits (<1 times per day in a week) (AOR = 2.69, 95% CI:1.34–5.40, P value 0.005). Conclusion The study reveals key GBC risk factors, offering vital insights for targeted screening, resource allocation, and public health measures to mitigate risks in Nepal.